Uvaria rufa Blume attenuates benign prostatic hyperplasia via inhibiting 5α-reductase and enhancing antioxidant status - Wararut Buncharoen (2018)
© 2016 Elsevier Ireland Ltd Ethnopharmacological relevance Traditional medicine has used Uvaria rufa Blume as an ethnomedicinal plant for treating fever, skin allergies, intestinal ulcers and prostate disorders including BPH. However, no scientific evidence supports the traditional use. Aim of the study This study aimed to evaluate the therapeutic potential of U. rufa on BPH using in vitro and in vivo models. Materials and methods In vitro studies screened the efficacy of a 5α-reductase (5αR) inhibition and antioxidant activity of petroleum ether, ethyl acetate, ethanol and aqueous extracts from the stem of U. rufa. Phytochemical screening was performed to determine the active compound using high-performance liquid chromatography (HPLC). Ethyl acetate extract (UR-EtOAc) of U. rufa was used to evaluate the therapeutic efficacy in vivo models. BPH was induced by subcutaneous injection of testosterone propionate (3 mg/kg) to male rats for 30 days. After 30 days of oral administration of UR-EtOAc at doses of 10 and 20 mg/kg and finasteride at a dose of 1 mg/kg, the prostate weight, prostate index (PI), testosterone and androgen receptor (AR) levels, and histopathological alteration of prostate gland were determined. Also, oxidative status and toxicity indices were assessed. Results UR-EtOAc exhibited the highest potency of inhibition of 5αR and possessed potent antioxidants rich in phenolics and flavonoids contents. The active compound analyzed by HPLC was β-sitosterol. In vivo results show a significant reduction in prostate weight, PI, and AR in all treated groups when compared to the BPH model group (P<0.001). Also, the UR-EtOAc and finasteride treated groups had increased prostatic and serum testosterone levels when compared to the BPH model group. A histopathological investigation of the prostate glands supported the above results. UR-EtOAc elevated the antioxidant enzymes and reduced the malondialdehyde level in BPH-induced rats. Moreover, treatment of UR-EtOAc at all doses had no toxic effects on the vital organs and serum biochemical indices. Conclusions UR-EtOAc from the stem of Uvaria rufa Blume appears to have the potential as a phytotherapeutic agent in the management of BPH, which provides the scientific evidence for traditional use.